2020
DOI: 10.1038/s41598-020-77242-4
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal estimation of the risk and the international transmission of COVID-19: a global perspective

Abstract: An ongoing novel coronavirus outbreak (COVID-19) started in Wuhan, China, in December 2019. Currently, the spatiotemporal epidemic transmission, prediction, and risk are insufficient for COVID-19 but we urgently need relevant information globally. We have developed a novel two-stage simulation model to simulate the spatiotemporal changes in the number of cases and estimate the future worldwide risk. Simulation results show that if there is no specific medicine for it, it will form a global pandemic. Taiwan, So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Generally speaking, it was observed that government-imposed mobility restrictions were successful in mitigating COVID-19 transmission [ 61 , 138 ]. At a global level, a positive correlation was found between human mobility and COVID-19 infections [ 45 , 92 , 75 , 76 , 139 ]. At a national scale, several studies found that mobility reduction generally implies a restrain on infections [ 59 , 140 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, it was observed that government-imposed mobility restrictions were successful in mitigating COVID-19 transmission [ 61 , 138 ]. At a global level, a positive correlation was found between human mobility and COVID-19 infections [ 45 , 92 , 75 , 76 , 139 ]. At a national scale, several studies found that mobility reduction generally implies a restrain on infections [ 59 , 140 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surveillance data, including phylogenomic analysis of clinical infections, has shown that the virus has evolved with highly transmissible variants, i.e., variants of concern (VOCs), including Alpha, Beta, Gamma, Delta, and Omicron. These variants have driven successive waves of transmission in different continents and territories [ 3 , 4 , 5 ]. Other reports have associated variant-specific outbreaks with different demographics and clinical forms of COVID-19, but whether these factors can explain the case disparities reported globally has not been thoroughly investigated [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The local gravity model based on power-law decay can effectively describe the diffusion patterns and process of COVID-19 in Hubei Province [16]. On a global scale, the risk of COVID-19 in each country decreased exponentially with the input of the first imported case and the time of onset [17]. At present, many types of COVID-19 vaccines are on the market.…”
Section: Introductionmentioning
confidence: 99%